Multisequencing of solutions of systems of equations of large dimension - Нагорний, Л. Я.; Жуков, І. А. (Proceedings of National Aviation University (archive), 1998)
Considered are the fundamental assumptions of decomposition and organization of multisequencing of algorithm of solution of large dimension linear equation systems with rarefied matrix. Due to specific characteristics of matrix block structure of equation coefficient system the processing of each block or equation subsystems can be carried out independently on some processor elements. In order to solve systems of large dimension equations formulated is a concept of formation of multilevel parallel calculating systems